2010
DOI: 10.1007/s10682-010-9364-7
|View full text |Cite
|
Sign up to set email alerts
|

The association among herbivory tolerance, ploidy level, and herbivory pressure in cardamine pratensis

Abstract: We tested whether differences in ploidy level and previous exposure to herbivory can affect plant tolerance to herbivory. We conducted a common garden experiment with 12 populations of two ploidy levels of the perennial herb Cardamine pratensis (five populations of tetraploid ssp. pratensis and seven populations of octoploid ssp. paludosa). Earlier studies have shown that attack rates by the main herbivore, the orange tip butterfly Anthocharis cardamines, are lower in populations of octoploids than in populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 59 publications
3
20
0
Order By: Relevance
“…Tolerance to damage was not correlated with plant resistance against oviposition estimated under controlled conditions. However, populations with higher attack intensities by A. cardamines in the field were more tolerant to larval herbivory under controlled conditions than populations experiencing low attack intensity [13]. We also confirmed that tolerance was not related to any costs in the absence of herbivory [13].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Tolerance to damage was not correlated with plant resistance against oviposition estimated under controlled conditions. However, populations with higher attack intensities by A. cardamines in the field were more tolerant to larval herbivory under controlled conditions than populations experiencing low attack intensity [13]. We also confirmed that tolerance was not related to any costs in the absence of herbivory [13].…”
Section: Discussionsupporting
confidence: 76%
“…Both ploidy types are used for oviposition by the butterfly Anthocharis cardamines , but tetraploid populations are often more attacked than octoploid populations [27]. A previous study with this study system [13] showed that average tolerance levels of populations were positively correlated with attack intensity in the field. The main question addressed in this study is how among-population variation in tolerance is related to variation in both resistance and attack rates among natural populations.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…As a consequence, we may expect populations at lower latitudes to have evolved greater defenses or increased tolerance to being eaten. Other work has found variation in tolerance among populations in a limited area (Bergelson and Crawley 1992, Juenger et al 2000, Banta et al 2010, Boalt et al 2010. Other work has found variation in tolerance among populations in a limited area (Bergelson and Crawley 1992, Juenger et al 2000, Banta et al 2010, Boalt et al 2010.…”
Section: Introductionmentioning
confidence: 98%
“…It also did not confirm the usually observed tendency towards better vegetative growth linked to clonality in polyploids, which in some cases contrasts with better generative reproduction in diploids (Č erná and Müenzbergová 2013;Henery et al 2010;Hroudová and Zákravský 1993). As pointed out by Boalt et al (2010), when examining tolerance to damage in populations of different ploidy, it is important to take into account other possibly linked factors such as phenology. As shifts in phenology promote sympatric speciation (Schluter 2001), phenological differences in different ploidy levels are to be expected.…”
Section: Ploidy Levelsmentioning
confidence: 91%